PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN POLIS ASURANSI PT. ASURANSI TOTAL BERSAMA - Amelia Arni Handaja; Darwin Raja Unggul Saragih (Panorama Nusantara, 2021)
This study aims to analyze the purchase decisions toward insurance products. Data collected through questionnaires instrument as primary data. The population of this research was customers in Jabodetabek area and outside Jabodetabek with the sample used in this study was 100 customers and the method used in sampling with certain criteria (purposive sampling) on condition that they had purchased an insurance policy. The analytical method used in this research is descriptive and quantitative methods. Processing of analytical data Structural Model Test (Inner Model) and Measurement Model Test (Outer Model) using application Smart PLS version 0.3. The results of the research conducted stated that there was a positive influence between brand image, price perception, and service quality on purchasing decisions with a percentage of 62.2%, while the rest was influenced by other variables.